2015
DOI: 10.11648/j.ijaas.20150102.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adding Manganese to Tris Extender on some Post-Cryopreservation Semen Attributes of Holstein Bulls

Abstract: Abstract:This study was conducted to explore the adding effect of manganese (Mn +2 ) to Tris extender on post cooling and cryopreservation semen attributes of Holstein bulls for different periods. Seven Holstein bulls of 3.5-4.5 years old were used in this study. Pooled semen was divided into three groups. The first group was diluted with Tris only (control group, G1). While the 2 nd (G2) and 3 rd (G3) groups were added 0.7 and 0.9 mM Mn +2 respectively. The effect of these additions on Holstein bulls semen qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The above could be attributed to high mitochondrial membrane potential maintained by sperm preserved with manganese. In a study by Eidan et al [ 37 ], the addition of Mn 2+ to a Tris extender significantly increased total counts (×10 6 ) of motile spermatozoa, improved acrosomal integrity and increased the counts of spermatozoa with normal morphology relative to control groups in different periods of the sperm production cycle. Manganese easily penetrates sperm cells, and maintains and restores the appropriate ion balance inside cells, thus minimizing the adverse effects of sperm preservation procedures [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above could be attributed to high mitochondrial membrane potential maintained by sperm preserved with manganese. In a study by Eidan et al [ 37 ], the addition of Mn 2+ to a Tris extender significantly increased total counts (×10 6 ) of motile spermatozoa, improved acrosomal integrity and increased the counts of spermatozoa with normal morphology relative to control groups in different periods of the sperm production cycle. Manganese easily penetrates sperm cells, and maintains and restores the appropriate ion balance inside cells, thus minimizing the adverse effects of sperm preservation procedures [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results in Table (2) showed that there were highly significant differences (P<0.01) in the percentage of live sperm after cooling, as the treatment (T2), which recorded (75.20 ± 0.37), excelled on the treatments T1, T3, and T4, which recorded (71.80 ± 0.58). (62.00±1.22) and 56.00±(1.70, respectively.…”
Section: Effect Of Adding Different Levels Of Nano-zinc Oxide On the ...mentioning
confidence: 96%
“…The fertility of bulls is considered an important issue in artificial or natural insemination of cows, in addition to its economic importance within breeding systems [1,2] . In the process of artificial insemination, the fertility of bulls is linked to the ability of the bull to produce sperm and fertilize the egg, by increasing the number of progressively motile sperm and reducing the rate of deformities in the semen, which in turn leads to an increase in the pregnancy rate in cows [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…The cow pregnancy rate increases with the number of progressively motile sperm, an increase in straw for artificial insemination, and depending on the freezability of sperm (29). Sperm freezability per bull varies by semen components, diluent types, and additives (20,21,44). Definition of freezability: the ratio of individual sperm motility after cryopreservation to individual sperm motility in fresh sperm (21).…”
Section: Introductionmentioning
confidence: 99%
“…Mart´ınez-Soto et al (35) indicated the possibility of using seminal fatty acids to predict cryopreservation ability in men. Many studies have shown the improvement of the cryopreservation ability and viability of the Holstein bull's sperm by adding fatty acids or omega-3 to the extenders (20,25,26,27,28). Argov-Argaman et al (10), AL-Gebour found and Eidan (4,5) a change in the many fatty acids concentrations in seminal plasma and sperm between the winter and summer seasons.…”
Section: Introductionmentioning
confidence: 99%